MANIFESTATIONS OF OSTEOPOROSIS IN SYSTEMIC DISEASES (Modern American Journal of Medical and Health Sciences, 2025)
In recent years, EULAR, European Osteoporosis Society, British Society of Rheumatology have recommendations for Osteoporosis treatment. Due to the variety of clinical manifestations and the severity of the prognosis, it is always difficult to choose a treatment strategy for patients with Osteoporosis.The need for timely diagnosis of PAG is determined by the need for early initiation of therapy.